Attempting near-infrared transillumination imaging with simple instrumentation for studying dental lesions - Thi Hai Mien Pham; Phu Duong Le; Thi Kim Tham Ta (Vietnam Journal of Science, Technology and Engineering, 2019)
During the past decades, near-infrared (NIR) methods have been applied to many aspects of life, particularly in dentistry. X-ray methods involve reliable techniques that dentists use to evaluate tooth structure lesions. However, X-ray methods still have some limitations, such as affecting patient health and dentists. In addition, early demineralised enamel is barely detected by X-ray methods. Many studies have demonstrated the usefulness of NIR light for observing tooth structure due to the differences of the optical properties between sound and demineralised tooth tissues under NIR wavelengths. Early demineralisation located under the enamel layer can be observed by NIR imaging (780-1,300 nm). The areas suspected to be demineralised enamel are distinct from the stain and pigmentation because stain and pigmentation do not appear in NIR images. The demineralised areas are substantially darker than the surrounding sound tissues under NIR light. In this study, two optical systems with transillumination and scattering techniques using NIR light (940 nm) were built for capturing occlusal and approximal images of teeth. The systems fulfill some requirements, such as simple setup, safety, and affordable price for the purpose of the replacement of imported equipment.